Capsicum - Dekebo, Aman (IntechOpen, 2020)
Capsicum, also known as chili or bell pepper, is one of the most economically important vegetable crops worldwide due to its antioxidant, anti-inflammatory, and anticancer properties. This book provides information on many aspects of this plant, such as its botanical information, nutritional values, bioactive compounds, pharmacology, cultivation, its use in treating diseases, and its applications in the food and pharmaceutical industries.